Islamic Jurisprudence in Academia: Knowledge Production and Interpretation at Indonesian Islamic Universities - Abdurrohman Kasdi; Fauzan Adim (KARSA Journal of Social and Islamic Culture, 2025)
This research is based on a literature review using historical and phenomenological approaches, interviews, and comparisons. This study seeks to understand the efforts of Indonesian Muslim academics in the study of al-Tafsir Al-Fiqhi in Islamic universities, focusing on the Al-Quran Science University (UNSIQ) in Wonosobo and PTIQ University in Jakarta. The data from this study were analyzed using content analysis, by analyzing data from theses, dissertations, and publications from UNSIQ Wonosobo and PTIQ University Jakarta, focusing on the methods of knowledge production. The steps taken in this study were as follows: First, the research data were described through references related to legal interpretation or fiqh, especially in Indonesia. Then, the theses and dissertations at UNSIQ Wonosobo and PTIQ University Jakarta were reviewed, and finally, all data were interpreted, induced, studied, and investigated. This research shows that the production of knowledge in al-Tafsir al-Fiqhi at UNSIQ Wonosobo and PTIQ Jakarta strengthens the role of al-Tafsir al-Fiqhi studies in dealing with legal and jurisprudential issues in Indonesia. In addition, both universities contribute to the production of research related to the interpretation of legal verses, which contributes to the revival of al-Tafsir al-Fiqhi studies. Furthermore, this study also shows that both universities focus on three things: First, improving understanding of legal texts, analyzing legal verses, and comparing them with the needs of society. Second, focusing on the development of educational and research methodologies by integrating Islamic traditions and Sharia objectives with the realities of Indonesia. Third, contributing to community service. It can be done by applying fiqh interpretations to practical issues, such as family law and financial transactions. UNSIQ Wonosobo and PTIQ Jakarta face challenges in their efforts, such as the need for more studies linking legal interpretation to the global context and balancing the preservation of classical fiqh heritage with the demands of the times.